The identity of Phlogacanthus curviflorus var. menchanensis (Acanthaceae) - Mehmud, Selim; Das, Kangkan Kumar; Chetia, Twinkle; Roy, Himu; Bhattacharyya, Debjyoti; Bujarbarua, Pranab; Borthakur, Sashin Kumar (Phytotaxa, 2023)
N/A